2013
DOI: 10.1088/1752-7155/7/2/026010
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen cyanide concentrations in the breath of adult cystic fibrosis patients with and without Pseudomonas aeruginosa infection

Abstract: Elevated concentrations of hydrogen cyanide (HCN) have been detected in the headspace of Pseudomonas aeruginosa (PA) cultures and in the breath of children with cystic fibrosis (CF) and PA infection. The use of mouth-exhaled breath HCN as a marker of PA infection in adults is more difficult to assess as some without PA infection generate HCN in their mouths. The analysis of breath exhaled via the nose, thereby avoiding volatile compounds produced in the mouth, will demonstrate elevated concentrations of HCN in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
66
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 31 publications
2
66
0
Order By: Relevance
“…The in vitro conditions affecting hydrogen cyanide release have been established [13, 14] and it is known that P. aeruginosa is the only organism frequently found in the CF lung that produces hydrogen cyanide [15, 16]. In vivo studies have demonstrated elevated exhaled breath hydrogen cyanide in both children and adults with CF and chronic P. aeruginosa infection, compared to controls [17, 18]. These studies demonstrated that hydrogen cyanide is a biomarker of chronic P. aeruginosa infection.…”
Section: Introductionmentioning
confidence: 99%
“…The in vitro conditions affecting hydrogen cyanide release have been established [13, 14] and it is known that P. aeruginosa is the only organism frequently found in the CF lung that produces hydrogen cyanide [15, 16]. In vivo studies have demonstrated elevated exhaled breath hydrogen cyanide in both children and adults with CF and chronic P. aeruginosa infection, compared to controls [17, 18]. These studies demonstrated that hydrogen cyanide is a biomarker of chronic P. aeruginosa infection.…”
Section: Introductionmentioning
confidence: 99%
“…Laser spectroscopy offers advantages for trace gas detection, in particular in speed, specificity, sensitivity and real-time detection. Laser-based spectroscopic methods have been widely used for sensing, such as laserinduced breakdown spectroscopy (LIBS) [9], cavity ring in exhaled breath of CF patients [24][25][26][27]. Cystic fibrosis itself is an inherited genetic disease, which is characterized by recurrent pulmonary infections and chronic lung inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] The second stage involves the analysis of exhaled breath samples taken from patients known to have pulmonary infection with the relevant pathogen. 9,10 This investigates if the VOCs identied in vitro can also be identied in vivo and attempts to assess the effect of host factors such as co-infection, dietary intake and diurnal variation. 11,12 If conrmed, further studies may be undertaken to investigate if the VOCs are detectable in exhaled breath early enough aer new infection to allow them to be used as a screening test.…”
Section: Introductionmentioning
confidence: 99%